2008
DOI: 10.1038/nature06616
|View full text |Cite
|
Sign up to set email alerts
|

Rapid appearance and local toxicity of amyloid-β plaques in a mouse model of Alzheimer’s disease

Abstract: Senile plaques accumulate over the course of decades in the brains of patients with Alzheimer's disease. A fundamental tenet of the amyloid hypothesis of Alzheimer's disease is that the deposition of amyloid-β precedes and induces the neuronal abnormalities that underlie dementia 1 . This idea has been challenged, however, by the suggestion that alterations in axonal trafficking and morphological abnormalities precede and lead to senile plaques 2 . The role of microglia in accelerating or retarding these proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

43
805
4
10

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 941 publications
(877 citation statements)
references
References 25 publications
43
805
4
10
Order By: Relevance
“…This is probably because these fibers arise from affected neurons, although we cannot exclude the possibility that this may be due to the neurotoxic effects of Aβ [6,24,34] . In another study, Meyer-Luehmann et al demonstrated in a mouse model of AD that plaques can grow overnight, with mature plaques originating from smaller amyloid deposits (microplaques) associated with alterations in neighboring neurites [35] . The origin of the microplaques is unclear, but our recent fi ndings suggest that they might be related to axonal leakage.…”
Section: Discussionmentioning
confidence: 99%
“…This is probably because these fibers arise from affected neurons, although we cannot exclude the possibility that this may be due to the neurotoxic effects of Aβ [6,24,34] . In another study, Meyer-Luehmann et al demonstrated in a mouse model of AD that plaques can grow overnight, with mature plaques originating from smaller amyloid deposits (microplaques) associated with alterations in neighboring neurites [35] . The origin of the microplaques is unclear, but our recent fi ndings suggest that they might be related to axonal leakage.…”
Section: Discussionmentioning
confidence: 99%
“…Two models could be proposed. At one extreme, plaques could cause local damage to the neuropil as they deposit, but then remain relatively static lesions 10 as the disease pathologic process becomes increasingly dominated by nonplaque pathologies, including tau-associated lesions such as neuropil threads and tangles, neuronal and synaptic loss, and noneplaque-associated glial reactions. 5 At the other extreme, plaques could increasingly contribute to local neural system destruction over the entire course of the disease.…”
mentioning
confidence: 99%
“…Alzheimer's disease (AD) is characterized by the progressive accumulation of extracellular amyloid  plaques, intracellular neurofibrillary tau, neuroinflammation, extensive neuronal cell death and dementia [126]. Increased expression of GRP78 was found in brain tissue of AD patients at the early pathological stage of AD compared to controls without dementia [127].…”
Section: Pdmentioning
confidence: 99%